Tumor maligno da bainha de nervo periférico envolvendo raízes nervosas do terceiro segmento medular lombar em um cão - Da Silva, Elisângela Olegário; Zanoni, Fabiana Pessuto; Ferioli, Raquel Beneton [UNESP]; De Souza, Mirian Siliane Batista; Di Santis, Giovana Wingeter (Universidade Estadual de Londrina, 2012)
Malignant peripheral nerve sheath tumors (MPNST) involving spinal nerve roots are uncommon in dogs. A nine-year old, intact, mixed-breed dog, demonstrated clinical signs of incoordination in the pelvic limbs and micturition for approximately one week. Clinical examination revealed proprioceptive deficits and bilateral patellar hyperreflexia. During exploratory celiotomy a mass was observed adhered to the lumbar vertebral segments. Medical therapy was initiated, but neurological signs were progressive, and the owner opted for euthanasia. Gross examination showed that the mass in the abdominal cavity was attached to the lumbar segments L3 and L4, causing bone lysis in L3, but showed no tumor invasion into the spinal canal. Microscopic features were characterized by prominent proliferation of ovoid and fusiform cells with poorly defined cytoplasm arranged in interlacing bundles and concentric whorls. The cells were embedded in a delicate to moderate collagenous stroma and moderate anisokariose and high mitotic activity were noted. The immunohistochemical assay showed positive staining for GFAP, S-100 protein and vimentin, and negative staining for factor VIII, α-actin and citokeratine. The definitive diagnosis of malignant peripheral nerve sheath tumor was made on the basis of the histological and immunohistochemical findings.
Canine malignant peripheral nerve sheath tumor involving nerve roots of the third lumbar spinal cord segment
Keywords: Dog; MPNST; Spinal nerve root